Placement of fluid viscous dampers to reduce total-building seismic damage - Del-Gobbo, G (2017)
Nonstructural damage has been found to critically influence economic losses and building downtime following earthquakes. Attaining a target level of seismic performance mandates the harmonisation of structural and nonstructural performance. Retrofitting buildings with fluid viscous dampers (FVDs) can improve interstorey drifts and floor accelerations, parameters which characterise seismic demands. The distribution of dampers within a building and the amount of supplemental damping are critical decisions. Many placement methods have been proposed, however no conclusive optimal method has been identified. The objectives of the thesis included benchmarking the performance of code-compliant buildings, investigating the optimal amount of damping, and comparing major damper placement methods. The seismic performance of Eurocode-compliant concentric braced frame buildings was benchmarked. Structures were modelled in OpenSees and the FEMA P-58 procedure was used to assess seismic performance in repair costs, a comprehensive measure of total-building performance. Buildings may be demolished following an ultimate limit state earthquake due to high repair costs. Storeys satisfying the Eurocode drift limit for nonstructural protection nevertheless experienced drift- and acceleration-sensitive damage. Most damage was attributed to nonstructural systems. Acceleration-sensitive damage is of comparable or greater consequence than drift-sensitive damage. These findings should be more appropriately reflected in structural design procedures. The optimal amount of damping to minimise repair costs was identified as 30-40%, larger than previously suggested levels based on structural parameters. Six damper placement methods were evaluated using linear FVDs. No method produced optimal results for both drifts and accelerations. Iterative methods that purport to optimise performance did not achieve that objective: local rather than global parameters are considered, and optimising for a single parameter may worsen another that impacts damage. The storey shear strain energy method and uniform damping produced repair costs more favourable than, or equal to, the other placement methods. Damper placement optimisation may be successful for high-rise or irregular structures.